Identifikasi Daun Sangkareho (Callicarpa longifolia Lam) secara Makroskopis dan Mikroskopis : Macroscopic and Microscopic Identification of Sangkareho (Callicarpa longifolia Lam.) Leaves - Helma Novitasari; Siti Nashihah; Irfan Zamzani (Jurnal Sains dan Kesehatan, 2021)
The utilization and development of traditional plants is a big investment for the sustainability of Indonesia society. Traditional medicine has its own requirements in order to guarantee the authenticity or correctness of the raw materials used. Sangkareho (Callicarpa longifolia Lam.) Is a family of Lamiaceae and a species of the genus Callicarpa. This study aims to provide scientific information data about the macroscopic and microscopic leaves of Sangkareho. The examination was carried out by observing the fresh leaves and the simplicia powder on the leaves of Sangkareho. The organoleptic results of the fresh Sangkareho leaves are hijua color, the distinctive smell of Sangkareho leaves is weak, and the taste is bitter, while the simplicia powder is slightly brownish in color, the distinctive smell of Sangkareho leaves is strong, and the taste is bitter. Macroscopic obtained by Sangkareho leaves are dark green on the upper surface and light green on the underside of the leaves, bitter taste, distinctive smell of Sangkareho leaves, oval elongated leaf shape, slightly hairy leaf surface, 11-17 cm long, 3 5-6 cm, the leaves are rather thin, the edges of the leaves are serrated, and the tips of the leaves are tapered, while for the simplicia powder it has a dense, smooth, non-stringy and dry texture, slightly brownish green, bitter taste, and has a distinctive smell of sangkareho leaves.